2001
DOI: 10.1346/ccmn.2001.0490302
|View full text |Cite
|
Sign up to set email alerts
|

Unusual X-Ray Characteristics of Vermiculite from Wiry, Lower Silesia, Poland

Abstract: Coarse-grained vermiculite from a serpentinite-pegmafite thermal zone displays a rational series of narrow 14.4 A basal reflections and an unusual broad 28 A peak. X-ray diffraction simulations and fitting techniques show that the 28 ,~ peak is related to 28 .~ domains consisting of elongated 2:1 layers of different lengths. The domains are located at the crystal edges of the vermiculite.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
3
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 13 publications
1
3
0
Order By: Relevance
“…A complete statistical analysis regarding the overall content of defects cannot be achieved because of the segregated nature of defects in different zones. Nevertheless, TEM observations obtained in the present study seem to corroborate the interpretation of Sakharov et al (2001). The layer-termination defects in Fig.…”
Section: Analysis Of Structure Defects In Natural Vermiculite Crystalsupporting
confidence: 89%
See 3 more Smart Citations
“…A complete statistical analysis regarding the overall content of defects cannot be achieved because of the segregated nature of defects in different zones. Nevertheless, TEM observations obtained in the present study seem to corroborate the interpretation of Sakharov et al (2001). The layer-termination defects in Fig.…”
Section: Analysis Of Structure Defects In Natural Vermiculite Crystalsupporting
confidence: 89%
“…Its position systematically corresponded to twice the position of the 001 reflection, which gradually shifted from $15 to $12.2 Å and finally to $10 Å (Hubert et al, 2013), clearly indicating that this additional reflection is related to the presence of layers with swelling properties. Similar structure analysis on a fine fraction of another type of natural vermiculite by Sakharov et al (2001) also showed the presence of a similar reflection at 2d 001 . These latter authors demonstrated that this diffraction feature could not be reproduced by considering ordered successions of layers with different chemistry.…”
Section: Analysis Of Structure Defects In Natural Vermiculite Crystalmentioning
confidence: 56%
See 2 more Smart Citations